Attentional bias, craving and cannabis use in an inpatient sample of adolescents and young adults diagnosed with cannabis use disorder: The moderating role of cognitive control. (January 2020) - Van Kampen, A. Dunkerbeck; Cousijn, J.; Engel, C.; Rinck, M.; Dijkstra, B.A.G.
Abstract: Motivational processes like attentional bias and craving have been related to substance use. However, results are inconclusive. The present cross-sectional study was designed to replicate and extend previous research by investigating the relationships between attentional bias, craving, cognitive control and (severity of) cannabis use in a sample of inpatient adolescents and young adults (aged 18–30) diagnosed with CUD according to DSM-5. Contrary to expectations, our sample did not show attentional bias for cannabis words, neither did attentional bias correlate with craving, cognitive control or (severity of) cannabis use. In line with our hypotheses, however, increased session-induced craving was correlated to more daily cannabis use and reduced cognitive control. Furthermore, participants who displayed reduced cognitive control used more cannabis per day. A bootstrapped hierarchical regression model showed that, contrary to expectations, cognitive control did not modulate the relationships between attentional bias, craving and cannabis use. This study highlights the unique role of craving in relation to cannabis use and extends previous findings that cognitive control appears to have no moderating role regarding cannabis use disorder. Based on our results, it might well be that the underlying mechanisms of cannabis use disorder differ from those in other substance use disorders. Highlights: CUD patients did not show an AB towards cannabis-related words. Session-induced cannabis craving was positively related to daily cannabis use, however not to the severity of CUD. Cognitive control did not moderate the relationships between AB/craving and the severity of CUD or daily cannabis use.